SCALE TO MEASURE STRESSFUL CHARACTERISTICS IN EDUCATIONAL ENVIRONMENTS: A CASE OF A MEXICAN UNIVERSITY (Proceedings of the International Conference on Education, 2021)
When students enter the university, they undertake a series of activities that can potentially stress them and cause their training experience to be not ideal for their learning. It is the responsibility of higher education institutions to provide an optimal environment to acquire knowledge and skills; therefore, they must have instruments that measure the degrees of stress generated. This study's objective was to determine a scale's psychometric properties that measure stressful characteristics in educational environments, namely Semestre i. A cross-sectional study with a survey design was carried out. Two hundred sixty-two university students participated, 122 of whom were men with a mean age of 22.6 (SD = 1.4), and 140 were women with a mean age of 22.1 (SD = 1.2). A scale comprised of saturation dimensions (11 items) and unpredictability dimensions (7 items) was obtained. An Exploratory Factor Analysis was performed with the Maximum Likelihood extraction method and oblimin rotation to determine the construct validity. It was possible to explain 52.3% of the variance (X2 = 2566.64, df = 153, p = .001; KMO = .92) in two dimensions, namely, high demand environment and unpredictable environment. Reliability was calculated through internal consistency using the Cronbach coefficient, obtaining an alpha value of .92. A parsimonious scale was obtained with the necessary evidence to conclude that valid and reliable data can be obtained, allowing the students' stressful educational contexts to be identified and modified or intervened to generate a healthy learning environment.
Keywords: Stress; Student; Scale; Semestre i; Educational Innovation; Higher Education